(untitled) (Development Service Industry Management, 2024)
The purpose of the article is to reveal the framework for assessing the potential of an enterprise’s economic security system. The content of the framework for assessing the potential of an enterprise’s economic security system is outlined, which includes the characteristics of the assessment object, requirements for assessment, users of assessment results, and directions for using such results. An understanding of the enterprise’s economic security system and its potential are provided. The characteristics of the economic security system’s potential as an assessment object are defined, and the content of each of these characteristics is disclosed. The article proposes requirements for assessing the potential of the economic security system of the enterprise and describes the content of each proposed requirement. The users of the assessment results for the economic security system’s potential are identified. The sources of their interest in the assessment results are demonstrated for each user. Possible directions for using results of the assessment of the enterprise’s economic security system’s potential are determined and they are considered for each identified user of such results.